Komunikasi Pemasaran Rajutan Bunga Mawar untuk Kesehatan Lansia: Bedak Dingin, Lulur, dan Aromaterapi Anti-Hipertensi - Nirwana, Maya Diah; Destrity, Nia Ashton; Utami , Ima Hidayati (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community empowerment program addresses the limited marketing communication capacity among elderly artisan groups in Bakalan Village, Malang Regency, particularly in promoting health-based rose knitting products. The main objective is to enhance the skills of elderly artisans in designing, producing, and marketing innovative rose-knitted items that support elderly well-being while preserving local culture. The method applied is a participatory approach that includes training, mentoring, and cyclical evaluation. The program focused on developing rose-knitted products tailored to the elderly, such as containers for cold powder and scrubs, anti-hypertensive aromatherapy pouches, and sun-protection hats. These innovations were supported by visual branding, authentic advertising messages, and digital promotion through platforms like Instagram and YouTube (@bungapuspaofficial), as well as publication in national media outlets such as Times Indonesia and Pendoposatu.id. The results indicate significant improvement in marketing communication strategies and increased product visibility. Although limited advanced knitting skills among some elderly posed challenges, younger participants were involved to ensure continuity and innovation. This collaborative process underscores the potential of rose-themed products not only to enhance elderly health but also to strengthen local identity through Islamic floral symbolism, particularly the rose. The program concludes that ongoing training and strategic marketing communication are vital for sustaining artisan-based health products, stimulating the local creative economy, and reinforcing cultural values in Muslim-majority communities.